HUBUNGAN MENONTON TELEVISI TERHADAP PERKEMBANGAN PERSONAL SOSIAL PADA ANAK PRA SEKOLAH - Agustina, Emi; Junitalius, Aldino (Akademi Keperawatan Pamenang, 2011)
The influence of media toward children is more, the higher technology and it intensity. Whereas parents do not have time to give attention, guidance, and control their children, Children spend much more time watching television than conducting others. The purpose of research is to analyze the correlation between watching television toward socio personal growth of pre school child. Research design used in the research is cross sectional. Population from 30 respondents and 30 samples, taking sample uses total sampling. The result of research is got of watching television is much more (16,6 %), more (36,67%), enough (46,66%), fairly enough (0%) and the social personal growth are very good (40%), good (16,67%), enough (26,66%), fairly good (16,67%) from the result of correlation test. That shows that there is significant 0,046 < 0, 05 means Ho is refused. Based on the result, concluded that there is correlation between watching television toward social personal growth of Pre school child with low category. Parents should be realizing it. How more the influence of watching Television is. Every parent has responsibility to control and give attention of their growth, therefore a little thing of the influence must be anticipated by parents either positive or negative impact shown by them.